Critical pedagogy and pedagogy critics in Physical Education: analysis in academic congresses in Brazil and Argentina (Agora for Physical Education and Sport, 2021)
The aim is to analyze knowledge productions and epistemological positions on criticism of the pedagogical models of Physical Education in Brazil and Argentina. As empirical field, two biggest specific disciplinary congresses of both countries were chosen: the Congresso Brasileiro de Ciências do Esporte (CONBRACE) and the Congreso Argentino de Educación Física y Ciencias (CEF&C). The works related to the “Epistemology of Physical Education” in the last two editions (2017 and 2019) were selected for this study. As a result, we observe a constant criticism of modernity as an objective and at the same time as a reason to establish criticisms of the pedagogy of Physical Education.
Keywords: Physical Education; critical pedagogy; Brazil; Argentina; knowledge production